Testing and Analysis of Secured AODV Routing Protocol - Eswari, S (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad hoc networking is a technology which works without requiring an already established infrastructure and centralized administration and provides for the cooperative engagement of a group of mobile nodes. In a mobile ad hoc network, each node can function as router and thus mobile nodes directly send messages to each other via wireless to a destination node beyond its transmission range by using other nodes as relay points. In recent years, research on mobile ad-hoc network is growing exponentially. In mobile ad-hoc network, abbreviated as MANET, transmission can be takes place without any use of wires. In this network, nodes are mobile and free to move in any directions. They send their messages to any other mobile nodes in the network. One of the protocol of MANET is AODV (Ad-hoc On demand Distance Vector) Routing Protocol. The main problem in this network is that the nodes in this network is frequently moving thereby the topology is changing frequently in MANET. Thus it is very much necessary for every node in the network to keep track of change so that an efficient packet transmission can be done. This is done by modeling the AODV routing protocol. In this paper, the network is modeled by using the Colored Petri Nets(CPN). CPN is the high level petri net that has the capacity of formally modeling and verifying complex system